Sistem Point Belajar Berbasis Web Untuk Meningkatkan Motivasi Belajar Siswa SMP - Desi Mahdalena; Indra Kanedi; Jhoanne Fredricka; Devina Ninosari; Riska Eka Aprianty (Jurnal Dehasen Untuk Negeri, 2024)
The development of information technology has significantly influenced the learning process in schools. However, many students still have limited understanding of how to utilize technology effectively for learning activities. This issue was also found among students at SMP Negeri 11 Bengkulu Tengah. This community service activity aims to increase students' learning motivation through the implementation of a web-based learning point system and provide knowledge about the use of internet technology in education. The methods used include preparation, socialization, system usage training, and evaluation. The results show that students gained better understanding of internet technology and experienced increased motivation to learn through the implementation of the learning point system. The system creates a more interactive and competitive learning environment among students. Therefore, this activity contributes to improving students' motivation and readiness in facing technological developments.